AN ANALYSIS OF TEACHERS’ STYLE IN TEACHING ENGLISH AT SMP NEGERI KARANG PANGGUNG - Tari, Ulan Tari (Universitas Negeri Surabaya, 2023)
The students successful in learning English do not far with teacher role who can increase student motivation in learning, because of that, need a research to know how the teacher transfer the material in classroom. The Objective of this research were to describe the teachers' style used in teaching English at SMP Negeri Karang Panggung, and to describe the dominance teaching style used by teachers. The subject in this research were teachers at SMP Negeri Karang Panggung. The researcher used descriptive qualitative method and the data were collected throught questionnaire and interview. Basen on the result of the data analysis, it could be concluded that teachers at SMP Negeri Karang Panggung user Interactional teaching style in teaching and learning process. Both of the teacher involve student to discuss the material, giving opinion, have a sense of dependent, make students easier to understand the material and make learning in class enjoy.